Friending the past : the sense of history in the digital age - Liu, Alan, 1953- (The University of Chicago Press, 2018)
Can today's society, increasingly captivated by a constant flow of information, share a sense of history? How did our media-making forebears balance the tension between the present and the absent, the individual and the collective, the static and the dynamic--and how do our current digital networks disrupt these same balances? Can our social media, with its fleeting nature, even be considered social at all? In Friending the Past, Alan Liu proposes fresh answers to these innovative questions of connection. He explores how we can learn from the relationship between past societies whose media forms fostered a communal and self-aware sense of history--such as prehistorical oral societies with robust storytelling cultures, or the great print works of nineteenth-century historicism--and our own instantaneous present. He concludes with a surprising look at how the sense of history exemplified in today's JavaScript timelines compares to the temporality found in Romantic poetry. Interlaced among these inquiries, Liu shows how extensive "network archaeologies" can be constructed as novel ways of thinking about our affiliations with time and with each other. These conceptual architectures of period and age are also always media structures, scaffolded with the outlines of what we mean by history. Thinking about our own time, Liu wonders if the digital, networked future can sustain a similar sense of history